1995
DOI: 10.1093/clinids/20.3.557
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Quinolone-Resistant Escherichia coli Bacteremia in Neutropenic Patients with Cancer Who Have Received Prophylactic Norfloxacin

Abstract: Between January 1988 and December 1992, 35 episodes of Escherichia coli bacteremia were identified in a series of 230 cases of bacteremia in neutropenic patients with cancer. Thirteen episodes (37%) were due to quinolone-resistant strains. Minimal inhibitory concentrations of norfloxacin ranged from 16 micrograms/mL to 128 micrograms/mL, and those of ciprofloxacin from 8 micrograms/mL to 64 micrograms/mL. The incidence of bacteremia due to quinolone-resistant E. coli increased from zero episodes per 1,000 hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
81
1
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(93 citation statements)
references
References 16 publications
6
81
1
5
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28] These studies showed changes in the bacteria responsible for the infections, because cirrhotic patients submitted to prophylaxis with norfloxacin were infected almost exclusively by gram-positive cocci and gram-negative bacilli were rarely observed because of the apparent absence of resistance to quinolones by these bacteria. [19][20][21][22][23][24]29 However, recent studies have shown an increasing incidence in the resistance of gram-negative bacilli to quinolones in the general population, [30][31][32] as well as in neutropenic [33][34] and cirrhotic 23,35,36 patients submitted to prophylaxis with these antibiotics. This is thought to be a result of the current widespread use of quinolones in these populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28] These studies showed changes in the bacteria responsible for the infections, because cirrhotic patients submitted to prophylaxis with norfloxacin were infected almost exclusively by gram-positive cocci and gram-negative bacilli were rarely observed because of the apparent absence of resistance to quinolones by these bacteria. [19][20][21][22][23][24]29 However, recent studies have shown an increasing incidence in the resistance of gram-negative bacilli to quinolones in the general population, [30][31][32] as well as in neutropenic [33][34] and cirrhotic 23,35,36 patients submitted to prophylaxis with these antibiotics. This is thought to be a result of the current widespread use of quinolones in these populations.…”
mentioning
confidence: 99%
“…This is thought to be a result of the current widespread use of quinolones in these populations. 23,30,31,34 The development of bacterial resistance is perhaps at present the most worrisome concern regards antibiotic prophylaxis in cirrhotic patients, because it might decrease the effectiveness of this method of prophylaxis. 11,37 In addition, bacteria resistant to prophylactic antibiotics could cause more severe infections in patients on prophylaxis than the infections developed by patients without prophylaxis.…”
mentioning
confidence: 99%
“…5 Prophylaxis with oral levofloxacin decreased bloodstream infections (BSIs) in one randomized placebocontrolled study, although patients were exclusively undergoing autologous transplantation, and most were receiving therapy for solid tumours rather than leukaemia or lymphoma. 7 The use of prophylactic oral fluoroquinolones remains controversial [8][9][10][11] and the effects of oral antibiotics used prophylactically may not equate to intravenous agents. 12 We and others have hypothesized that pre-emptive intravenous antibiotic therapy, that is, antibiotics commenced at onset of neutropenia or on day of transplant (also referred to as prophylactic antibiotics in some recent publications), would reduce the incidence of fever and bacterial infection during the acute phase of transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…A introdução de fluoroquinolonas, grupo ao qual pertencem a norfloxacina e ciprofloxacina, na década de 80, significou, sem dúvi-da, um avanço no tratamento de infecções por bactérias multirresistentes, particularmente infecções do trato urinário (ITU) [2][3][4] , visto que diversas cepas de bactérias resistentes a múltiplos antimicrobianos mostraram-se sensíveis a esse novo grupo de medicamentos 5,6 . Trabalhos mais recentes, no entanto, têm alertado para um aumento da freqüência de bactérias resistentes às quinolonas [7][8][9][10] . Esse problema tem sido observado principalmente em pacientes com septicemias graves causadas por bactérias provenientes do trato urinário [8][9][10] .…”
Section: Introductionunclassified
“…Trabalhos mais recentes, no entanto, têm alertado para um aumento da freqüência de bactérias resistentes às quinolonas [7][8][9][10] . Esse problema tem sido observado principalmente em pacientes com septicemias graves causadas por bactérias provenientes do trato urinário [8][9][10] . O presente estudo foi realizado com o objetivo básico de avaliar possíveis modificações, ao longo dos anos, na sensibilidade à norfloxacina e ciprofloxacina de bactérias isoladas de uroculturas provenientes de pacientes ambulatoriais e hospitalizados de um Hospital Universitário localizado em Salvador, BA.…”
unclassified